2019
DOI: 10.19080/jgwh.2019.15.555915
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and Reproductive Health Services Utilization and Associated Factors Among University Students, Northwest Ethiopia: Cross Sectional Study

Abstract: Introduction: Students in higher institutions of learning are exposed to diverse sexual and reproductive health problems, such as unintended pregnancies, Human Immuno Virus/Aquired Immuno Deficiency Syndrome, sexually transmitted infections, and unsafe abortions. Despite diverse efforts to improve student use of sexual and reproductive health services, there is still limited evidence on the level of university student use of the available sexual and reproductive health services at university set-ups. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Globally, studies show higher socioeconomic status is related to the better chance of having sexual and reproductive information (2,3,9,17,18) through accessing different media and visiting health facilities and seeking related healthcare services, which directly or indirectly invest on sexual and reproductive health issues (2,3,8,9,(17)(18)(19)(20). On the other hand, previous studies conducted in Ethiopia were more focused on the utilization of sexual and reproductive health services (18,20,21) which could be difficult to increase unless we boosted youth sexual and reproductive health literacy (1)(2)(3)9).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, studies show higher socioeconomic status is related to the better chance of having sexual and reproductive information (2,3,9,17,18) through accessing different media and visiting health facilities and seeking related healthcare services, which directly or indirectly invest on sexual and reproductive health issues (2,3,8,9,(17)(18)(19)(20). On the other hand, previous studies conducted in Ethiopia were more focused on the utilization of sexual and reproductive health services (18,20,21) which could be difficult to increase unless we boosted youth sexual and reproductive health literacy (1)(2)(3)9).…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy test/care was another reported behaviour in two studies with prevalence of 5% (32)and 16.8% (34). Five studies out of fteen described risky sexual behaviour (23,24,33,36,38). Among them, two studies (23,33) did not quantify the prevalence while three studies quanti ed the prevalence as 30.2%(38) ,31%(36) and 44% (24).…”
Section: Resultsmentioning
confidence: 99%
“…Concerning behaviours, experiences, outcomes in the reviewed studies, surprisingly, all studies reported sexual activity and the prevalence was ranged from 18.9-79.5% (20,23,24,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39).Among this, 2 studies had reported both the past (61.1% and 28.4%) and current (73.5% and 53.1%) status of sexual activity among participants (20,29) while the rest of studies (23,24,28,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) reported only the status of sexual activity at the time of the study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations